PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU SD NEGERI SE KECAMATAN DUMAI BARAT KOTA DUMAI - Syafruddin Syafruddin; Isjoni Isjoni; Afrianto Afrianto (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2021)
The purpose of this study was to determine the effect of principal's leadership and teacher's work motivation, either individually or jointly on employee performance. The research was conducted in SDN in Dumai Barat sub-district, Dumai City with the research subjects being teachers in SDN in Dumai Barat sub-district, Dumai City, the method used was a survey with correlation technique, the research sample was teachers at SDN in the sub-district of West Dumai City. Dumai totaling 150. The instrument used to collect data on principals' leadership, work motivation and performance was using a questionnaire. The validity of the test items using the product moment formula and the instrument reliability coefficients were calculated using the Cronbach alpha formula. The results of this study indicate that: 1) there is a significant and positive influence between the principal's leadership on performance; 2) there is a significant and positive effect between teacher work motivation on performance; 3) there is a significant and positive influence between the principal's leadership and the work motivation of teachers on performance together. The results of this study are expected to be useful for the improvement and improvement of the performance of principals and teachers in public elementary schools throughout the West Dumai sub-district, Dumai City.